2011
DOI: 10.4012/dmj.2010-157
|View full text |Cite
|
Sign up to set email alerts
|

Dentin bonding: Influence of bonded surface area and crosshead speed on bond strength

Abstract: This study investigated the influence of the bonded surface area and the crosshead speed on the dentin bond strengths of self-etch adhesives. Bovine mandibular incisors were mounted in self-curing resin and the facial surfaces were wet ground with #600 silicon carbide (SiC) paper. The dentin surfaces were treated according to the manufacturer's instructions. Adhesives were applied, and the resin composites were condensed into molds (2.4 or 4.0 mm in internal diameter), placed on to the dentin, and then light a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…Our previous report found no significant interactions between these factors and the bonded surface area or crosshead speed; however, our data indicated that the shear bond strength of the adhesives tested depended on the bonded surface area and the crosshead speed (Fig. 6) [44,45].…”
Section: Influence Of Crosshead Speed On Bond Strengthcontrasting
confidence: 72%
“…Our previous report found no significant interactions between these factors and the bonded surface area or crosshead speed; however, our data indicated that the shear bond strength of the adhesives tested depended on the bonded surface area and the crosshead speed (Fig. 6) [44,45].…”
Section: Influence Of Crosshead Speed On Bond Strengthcontrasting
confidence: 72%
“…Dynamic loading of the tested materials and bonding them to different tooth structures might effect the resin bonding and its durability. In addition, different bond test methods might result in varying results, as it is known that the size of bonding area will affect the measured bond strength [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to obtain precise and consistent bond strength data due to the use of numerous testing techniques and parameters [3,4]. For example, some factors affect testing results, such as different adhesive areas, the crossing speed, the selection and preparation of substrate, the direction of shear force, and so on [5,6]. Therefore, an accurate and unified laboratory evaluation method is crucial for the effective clinical application of different adhesives, and just as important, differences in the testing procedures should be identified and standardized for consistency.…”
Section: Introductionmentioning
confidence: 99%